Pengembangan Perangkat Pembelajaran Matematika Berbasis Flipped Classroom pada Sekolah Menengah Pertama - Lilik Handayani; Pardimin Pardimin; Zainnur Wijayanto (Universitas Sarjanawiyata Tamansiswa, 2021)
This study aims to develop a flipped classroom based mathematics learning tool for building flat-side space in junior hidg schools. This study uses the research abd development method with a 4D model that is modified into 3D due to the covid-19 pandemic, so it pnly contains the define, design, and develop proceses. The results showed that the average validation result by expert validators for RPP was 4,4 (very valid) and the average validation result by stakeholders was 4,65 (very valid). The average result of validation by expert validation for LKPD is 4,49 (very valid) and the average result of validation by stakeholder is 4,74 (very valid). So that the result of the evaluation of the lesson plan by the experts and stakeholders obtained a mean score of 4,53, while the overall mean of the evaluation result of the LKPD by the expert validator and stajeholder obtained a mean score of 4,6. This shows that the flipped classroom based mathematics learning device in junior high school is suitbale for uses as a reference for learning mathematics subjects.